Basic English Speech Support And Pronunciation Skills Of Senior High School Students - Alperito, Henry Orbasayan; Ambayon, Cristobal Millenes (Advances in Social Sciences Research Journal, 2021)
The Basic English Speech Support is audio with transcription which is composed of the features of pronunciation that is purposely compiled to enhance pronunciation skills specifically, the sounds of English, stress, intonation, and linking. It is applied within the study with the aim of measuring its effectiveness to the pronunciation skills of Senior High School students. The study is designed to evaluate, validate and determine the effectiveness of Basic English Speech Support to the Senior High School, Grade 12, Accountancy, Business and Management students in Libertad National High School. English-teacher Evaluators evaluated the audio and its transcription. The design involved the experimental group and the control group which were carefully selected through the randomization process. The data gathered were analyzed using both descriptive and inferential tools such as mean, standard deviation, and t-test. The results revealed that students from the experimental group got a higher mean gain compared to the control group. It was factually and statistically confirmed that the utilization of Basic English Speech Support served as a significant element in teaching pronunciation and evidently, advances better learning among Senior High School students.